Geoelectrical Models of Glacial-Permafrost Rock Formations of the Central Altai - G. Dyakova S.; A. Goreyavcheva A.; A. Shein N.; V. Potapov V.; R. Burym D.; O. Ostanin V.; V. Olenchenko V.; Г. Дьякова С.; А. Гореявчева А.; А. Шеин Н.; В. Потапов В.; Р. Бурым Д.; et al. (IGRAS, 2024)
Geophysical observations of the structure of glacial-permafrost rock formations (hereinafter referred to as GPRF), common in the Central Altai in the valleys of the Chuya, Dzhelo, Elangash and Akkol rivers, were carried out by way of electrical resistivity tomography using the multi-electrode electro-prospecting station “Skala-48”. The main objective of the research was to identify the features of the internal structure of GPRF basing on the data of electrical sounding and aerial photography. The application of the geophysical method made it possible to localize rock-ice cores within the GPRF. Analysis of the geoelectrical crosssections allowed finding that the rock-ice cores were characterized by high values of specific electrical resistance (SER) – from 10 to 100 kOhm × m and more. The depths of occurrence of rock-ice material on the geoelectrical sections varied from 2 to 10 m, on the average. Using the data of the aerial photography carried out above the studied areas, three-dimensional geoelectric models and maps of the distribution of SER were built for different depths. When analyzing the three-dimensional model of the GPRF, it is clearly noticeable that the features of the nature of the SER distribution reflects the inhomogeneous distribution of ice within the rock-ice core of the GPRF. As a result of our studies performed by the method of electrical tomography and interpretation of a three-dimensional geoelectric model, it was estimated that thicknesses of the rock-ice material varied from 7 to 32 m, thawing niches were revealed and localized, and the potential volume of the rock-ice core was determined. Thus, the above mentioned geophysical and geomorphological studies in that the features of the internal structure of GPRF in key areas have been established. For each GPRF, the thicknesses, resistivity, and depth of occurrence of rock-ice cores were determined, and the dependence of the morphological structure of the GPRF surface on internal structure of them was analyzed. A preliminary assessment of ...